2007
DOI: 10.1007/s00204-007-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and allele frequencies of polymorphic CYP2E1 in the Turkish population

Abstract: Cytochrome P4502E1 (CYP2E1) gene shows genetic polymorphisms that vary markedly in frequency among different ethnic and racial groups. We studied the genotype distributions and allele frequencies of three CYP2E1 polymorphisms: CYP2E1*5B (RsaI/PstI RFLP, C-1053T/G-1293C SNP, rs2031920 /rs3813867), CYP2E1*6 (DraI RFLP, T7632A SNP, rs6413432), and CYP2E1*7B (DdeI RFLP, G-71T SNP, rs6413420) by PCR/RFLP technique in a sample of 206 healthy subjects representing Turkish population. CYP2E1*5B polymorphism analysis y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“…In addition, our results are in contrast with the fi ndings for the Turkish population reported by Takeshita et al (17), whose genotype distribution and allele frequencies are similar to those of African, Brazilian, and Eastern Asian populations. This is rather unexpected because polymorphism frequencies of xenobiotic metabolising enzyme genes studied in the Turkish population so far, namely CYP, mEH, and GST, are generally similar to other Caucasian populations (20)(21)(22)35). At this stage, we can only speculate about the reasons why our fi ndings differ, as both studies used the same methods, and sample sizes were similar.…”
Section: Resultsmentioning
confidence: 62%
“…In addition, our results are in contrast with the fi ndings for the Turkish population reported by Takeshita et al (17), whose genotype distribution and allele frequencies are similar to those of African, Brazilian, and Eastern Asian populations. This is rather unexpected because polymorphism frequencies of xenobiotic metabolising enzyme genes studied in the Turkish population so far, namely CYP, mEH, and GST, are generally similar to other Caucasian populations (20)(21)(22)35). At this stage, we can only speculate about the reasons why our fi ndings differ, as both studies used the same methods, and sample sizes were similar.…”
Section: Resultsmentioning
confidence: 62%
“…Distribution of CYP2E1 RasI/PstI alleles (c1, c2) and DraI alleles (D, C) varies much in different races [3,13] . Frequencies of allele c2 and C are 4% and 11% in European-Americans, 1% and 8% in African-Americans, 28% and 24% in Taiwanese [13] , 1.94% and 8.25% in Turkish population, respectively [3] .…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome P450 2E1 (CYP2E1) is a main 1111111  member of CYP450 family. CYP2E1 RsaI/PstI (c2) polymorphism has G→C substitution at 1293bp in 5'-untranslated region of CYP2E1 gene and introduces PstI restriction enzyme site, CTGCAǁG [3] which causes a decrease in enzymatic activity. CYP2E1 DraI (C) polymorphism has a T→A substitution at 7632bp in sixth intron and destroys the DraI restriction enzyme site [3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analyses have reported that the CYP2E1 RsaI/ PstI c2 allele is a protective factor for developing lung cancer among Asians and all ethnic population (Wang et al, 2010b;Zhan et al, 2010). However, it is well established that the frequencies of CYP2E1 RsaI/PstI polymorphisms differ markedly among different ethnic and racial groups (Soya et al, 2005;Ulusoy et al, 2007;Shahriary et al, 2012;Lakkakula et al, 2013). Therefore, it is necessary to address this issue in different ethnic groups.…”
Section: Introductionmentioning
confidence: 99%